Short pineapple-leaf-fiber-reinforced low-density polyethylene composites - George, J.; Bhagawan, S. S.; Prabhakaran, N.; Thomas, S.
Short pineapple-leaf-fiber-(PALF)-reinforced low-density polyethylene (LDPE)composites were prepared by melt-mixing and solution-mixing methods. In the melt-mixing technique, a mixing time of 6 min, rotor speed of 60 rpm, and mixing temperature of 130°C were found to be the optimum conditions. Tensile properties of melt-mixed and solution-mixed composites were compared. Solution-mixed composites showed better properties than melt-mixed composites. The influence of fiber length, fiber loading, and orientation on the mechanical properties has also been evaluated. Fiber breakage and damage during processing were analyzed from fiber distribution curve and optical and scanning electron micrographs. Considering the overall mechanical properties and processability characteristics, fiber lenght of 6 mm was found to be the optimum length of pineapple leaf fiber for the reinforcement in LDPE. The mechanical properties were found to be enhanced and elongation at break reduced with increasing fiber loading. Longitudinally oriented composites showed better properties than randomly and transversely oriented composites. Recyclability of the composite was found to be very good. A comparison of the properties of the PALF-reinforced LDPE composites with those of other cellulose-fiber-reinforced LDPE systems indicated superior performance of the PALF-LDPE composites.
Keywords: FIBER; REINFORCED; PLASTICS